THE MEANING OF SIGNS IN â€œBREAST CANCER SURVIVORâ€™S FIRST HAIRCUTâ€ ULTA BEAUTY ADVERTISEMENT - Yugiastari; Eka Pratiwi Desak Putu; Devi Maharani Santika I Dewa Ayu (Universitas Warmadewa, 2021)
The meaning of signs in advertisements is very important to make it easier for the audience to understand the content and purpose of the advertisement. This study aims to discover the meaning of verbal and nonverbal signs and discover the meaning of verbal and nonverbal signs found in the